Efficacy analysis of 26 cases of ejaculatory duct obstruction treated by prostatic utricle neck endoscopy - Lv, Kun-Long; Sun, Wen-Gong; Zhang, Tian-Biao; Zheng, Tao; Nan, Yong-Hao; Liu, Yong-Fei; Zhou, Yi-Fan; Wang, Rui (Frontiers in Surgery, 2022)
Background: The present study aims to evaluate the safety and effect of prostatic utricle neck fenestration under transurethral seminal vesiculoscopy in the treatment of ejaculatory duct obstruction. Methods: The clinical data of 26 male patients with infertility and ejaculatory duct obstructon who were treated in the Andrology Department of the First Affiliated Hospital of Zhengzhou University between June 2020 and February 2021 were retrospectively analysed. A low-energy holmium laser was used to help penetrate the neck of the prostatic utricle; the vesiculoscope could then be inserted into the ejaculatory duct. The patients' general clinical characteristics, intraoperative conditions and surgery effects were collected. Results: The ejaculatory duct was found through fenestration, and the seminal vesicle glands were entered into smoothly in 25 patients (96.2%). Among these patients, 22 underwent bilateral endoscopy and 3 underwent unilateral endoscopy. Sperm appeared in 23 cases (88.5%) at three months after operation. The sperm concentration and motility were higher at six months after operation than at three months after operation. No postoperative complications, such as epididymitis and retrograde ejaculation, occurred. Conclusion: Low-energy holmium laser-assisted fenestration of the prostatic utricle neck is a new treatment method for ejaculatory duct obstruction; it has a high success rate, good postoperative effects, and few complications.